The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3906/biy-1511-26
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic induction via membrane/DNA damage and metabolic inactivation by synthetic food colorants in Allium cepa root meristem

Abstract: The present study investigates the cytotoxic and genotoxic effects of two frequently employed synthetic food colorants, lemon yellow and orange red, using an Allium cepa assay. Uptake of food colorants by root cells at different concentrations and varied exposures significantly altered the cytogenetic system, membrane integrity, mitochondrial function, root growth, and cell division. The food colorants induced significant DNA damage, micronucleus formation, and other severe chromosomal aberrations at genetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(48 reference statements)
1
2
0
1
Order By: Relevance
“…The maximum inhibition of root lengths was observed at the highest concentrations. These results are in accordance with Vazhangat and Thoppil (2016) who found a significant decrease in A. cepa root length.…”
Section: Determination Of Ec 50 Valuessupporting
confidence: 93%
See 1 more Smart Citation
“…The maximum inhibition of root lengths was observed at the highest concentrations. These results are in accordance with Vazhangat and Thoppil (2016) who found a significant decrease in A. cepa root length.…”
Section: Determination Of Ec 50 Valuessupporting
confidence: 93%
“…It was observed that root lengths decreased with increasing concentration. In previous studies which evaluated the toxic effects of carmoisine, sunset yellow and other azo dyes on plants, it was determined that these colorants cause DNA damage, apoptotic cell death and mitotic abnormalities by reducing root length and cell division (Gomes et al 2013;Dwivedi and Kumar 2015;Vazhangat and Thoppil 2016). The maximum inhibition of root lengths was observed at the highest concentrations.…”
Section: Determination Of Ec 50 Valuesmentioning
confidence: 99%
“…De manera que, la prueba de A. cepa aprovecha la consecuencia de la disminución del índice mitótico, expresada en el menor desarrollo radicular, observando así diferencias significativas entre compuestos a distintas concentraciones, y tiempos de exposición. [12,13,14]. Por lo anterior, el objetivo de este estudio fue resaltar la aplicabilidad de la prueba de índice mitótico en células meristemáticas de A. cepa y comparar los datos del % IM obtenido en condiciones ambientales controladas con los % IM reportados en otros estudios en el ensayo control.…”
Section: Introductionunclassified
“…Hence instead of synthetic colorants, natural ones can promote a perfect and healthy life. Earlier studies on the induction of giant cells [1] and apoptotic activity and DNA damage as well as metabolic inactivation [2] had proved the cytotoxicity of some common synthetic food dyes. T. paniculata is an important dye yielding plant belonging to Combretaceae.…”
Section: Introductionmentioning
confidence: 99%